Pulse Electropolymerization and Thermoelectrical Performances of Carbon Nanotubes/Polyaniline Composite Film. (19th February 2016) - Liu, Xiaoqing; Yang, Weifang; Xu, Han; Wang, Wei
Abstract : The polyaniline (PANI) films and carbon nanotubes/polyaniline (CNTs/PANI) films were obtained by the method of pulse electropolymerization on Ni substrates coated by polyaniline films in sulfuric acid system. The effects of the variables such as pulse height (φ1 ) and relaxation time (t2 ) on film morphologies and thermoelectrical performances were studied. Film morphologies were investigated using the method of scanning electron microscope (SEM) and thermoelectrical performances of these films were determined by Seebeck coefficients, resistivities, as well as power factors. Results reveal that proper pulse parameters would make composite film present uniform chain fibers and visible knot-like protrusions, which is beneficial to improve the electrical conductivity and increase the power factor. Moreover, it was found that embedding CNTs was advantageous to increase the fiber aspect ratio of PANI and further improve the thermoelectrical performances, when comparing the properties of CNTs/PANI composite films with that of pure polyaniline films synthesized at the same conditions.